The Influence of “Using the Temple Property for Schools” Movement on the Organization of Han Buddhist Monastic Education in Modern China - Yonghui Hu (Religions)
Under the influence of “Using the Temple Property for Schools”(UTPSs) movement, the monastic education of Han Buddhism 漢傳佛教僧教育 in modern China, as a whole, has gradually moved towards the mode of Buddhist colleges, through the establishment of the Buddhist Educational Affairs Public Office (BEAPO) 佛教學務公所, the Institution of Monastic Education (IME) 僧教育會, and the institution of Buddhist education 佛教教育機構 with international outlook and has become the prototype of the educational institution of Han Buddhism in contemporary China. The attempts to run schools during the period of the BEAPO at the late Qing Dynasty objectively stimulated the awakening of the consciousness of the Buddhist community to establish schools and to promote education 辦學興教 and became the precursor of the rise of the wave of monastic education after the Xinhai Revolution, especially since the 1920s. The goal of “uniting the national Buddhism” proposed by the BEAPO became the direction for the development of subsequent Buddhist organizations. The BEAPO also accumulated experiences for the construction of later Buddhist organizations and stimulated the awakening of the monks’ sense of subjectivity. The organizational structure and many ideas of the BEAPO were later inherited by the IME; most of the contents of the constitution of it were also inherited and improved by the IME. As a Buddhist organization, the BEAPO made positive efforts to reconcile the tensions between monks and laypeople under the context of UTPS at that time. After the Xinhai Revolution, the Han Buddhist community focused on interacting with secular society, and the practice of Buddhist education reflected the awakening of self-consciousness to “establish schools to promote education”. In terms of the school operation mode, the diversified curriculum and modernized academic system reflect the characteristic of a balance between internal and external studies. During this period, the establishment of Buddhist educational institutions with an international outlook provided a guarantee of talent for the path of the “universalization” of Han Buddhism, as well as provided continuity for the sustainable development of it. Under the influence of the two UTPS movements, the tortuous development of Han Buddhist monastic education in modern China is, in fact, the epitome of the situation of the whole Chinese Buddhism in modern society. At the same time, it also reflects the proactive adaptation of Chinese Buddhism, in modern times, to external pressures and its self-remodeling in the struggle for survival space.